Preludium do rozważań o polskiej kulturze narodowej - RODZIŃSKI, Adam (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2014)
The author holds that Polish national culture was shaped by the history of Poland, which not infrequently involved building the state from scratch. Due to this fact the Poles have become a people keeping a healthy distance towards the mundane matters and they tend to focus on the spiritual instead. Therefore it is perhaps easier for the Poles to feel persons than it is for other nations, although they are not a nation of individualists or non-conformists. The Poles need and wish to share the responsibility for matters to which, due to the Polish history, they cannot stay indifferent. This responsibility, which affi rms human dignity and human subjectivity, may contribute to the Poles’ becoming not only better citizens, but also better human beings. Tekst artykułu za: Z Karolem Wojtyłą myśląc Ojczyzna, red. W. Chudy, Instytut Jana Pawła II KUL–Towarzystwo Naukowe KUL, Lublin 2002, s. 53-56. Po raz pierwszy artykuł opublikowany został w roku 1988 („Ethos” 1(1988) nr 4, s. 148-150).